Development of two dimensional solver code for hybrid model of energy absorbing system - Ahmad, Zaini (Academic Journals, 2013)
This paper treats the dynamic and energy absorption responses of nonlinear spring-mass system using a developed two dimensional solver code. The influence of spring stiffness and various mass configurations on the impact response was investigated using validated models. Results are quantified in terms of important impact response and indicate that an assembly of spring-mass system can be employed to examine the impact response of energy absorption system prior to the detailed numerical analysis and experiment. The developed solver code will be useful for educational purposes to preliminarily understand the behavior and impact response of energy absorbing system without learning a piece of complicated nonlinear commercial finite element codes namely LS-DYNA. The developed code could facilitate the early stage of evaluation for impact applications.